The Relationship between Applied Linguistics and Language Discourse Analysis in English Language Teaching - I Nengah Laba; Putu Chrisma Dewi (International Journal of Linguistics and Discourse Analytics, 2023)
This paper examines the relationship between applied linguistics and language discourse analysis in English language teaching (ELT). It explores the significance of these fields in enhancing language learning and teaching practices. The article discusses the theoretical foundations of applied linguistics and language discourse analysis. This study shows that applied linguistics and language discourse analysis share a close relationship as they both investigate language use and its practical applications. To effectively implement applied linguistics and language discourse analysis in English language teaching, it is essential to recognize the diversity of students' linguistic and cultural backgrounds. This can be achieved through a variety of approaches, including the use of discourse in language teaching and cultural responsive teaching. Applied linguistics and language discourse analysis make significant contributions to English Language Teaching (ELT) by providing insights, frameworks, and practical applications that enhance language learning and teaching processes. The significant contributions that applied linguistics and language discourse analysis have made to English Language Teaching (ELT), there is a strong call for continued research and implementation of these approaches in language teaching contexts. Furthermore, future research should focus on the effectiveness of different approaches and techniques in promoting applied linguistics and language discourse analysis in English language teaching.